Cultural Humility with Lesbian, Gay, Bisexual, and Transgender Populations: A Novel Curriculum in LGBT Health for Clinical Medical Students - Hilary Grubb; Hilda Hutcherson; Jonathan Amiel; Jane Bogart; Justin Laird (Association of American Medical Colleges, 2013)
Abstract Lesbian, gay, bisexual, and transgender (LGBT) individuals encounter documented health disparities in the United States, perpetuated in part by limited LGBT-related content in medical education curricula. This 2-hour curriculum in LGBT health and cultural humility for clinical medical students is a response to these documented curricular deficits and health disparities. This curriculum includes precurricular readings, a 1-hour didactic lecture, and a 1-hour panel of LGBT-identified individuals that is followed by an interactive question-and-answer session and public discussion. Pre- and postcurriculum surveys were conducted to determine if this LGBT curricular intervention led to short-term changes in clinical medical students' experiences, attitudes, and knowledge with respect to LGBT patient populations. Of the 11 medical knowledge questions, the mean precurriculum score was 6.6 correct answers, and the mean postcurriculum score was 8.6 correct answers. These results indicate that although students had limited prior clinical experience with LGBT patients and despite the small sample size, this curriculum led to robust and statistically significant increases in medical knowledge and positive shifts in attitudes with respect to LGBT populations.